PENERAPAN KESEHATAN DAN KESELAMATAN KERJA DI WORKSHOP TATA BUSANA SMK NEGERI 1 AMPEK ANGKEK AGAM - Sovia, Ray; Ernawati, Ernawati; Idrus, Yenni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2012)
This study revealed on the Application of Health and Safety (K3) in dressmaking workshop SMK State 1 Ampek Angkek Agam, terms of three indicators, that is (1) Application of K3 with itself, (2) Application of K3 in using the tools of practice, (3) Application of K3 in the work environment. This research is a qualitative study, in order to examine the condition of the natural objects with the intent of exposing some of the circumstances in which the researcher as the key instrument. Source of data obtained through informants who understand about the workshop are: students, teachers who teach subjects practice, the head of the workshop, head of the study program. Data was collected by observation, interviews, and documentation. The validity of the data is done by way of extension of participation, persistence observation, triangulation and auditing. The results showed that the application of K3 in dressmaking workshop SMK State 1 Ampek Angkek Agam on each indicator has not been fully implemented at the time of practice.